Advances by the Marie Curie project TANGO in thermoacoustics. (May 2019) - Heckl, Maria
This paper gives an overview of the research performed by the project TANGO – an Initial Training Network (ITN) with an international consortium of seven academic and five industrial partners. TANGO is the acronym for 'Thermoacoustic and Aeroacoustic Nonlinearities in Green combustors with Orifice structures'). The researchers in TANGO studied many of the intricate physical processes that are involved in thermoacoustic instabilities. The paper is structured in such a way that each section describes a topic investigated by one or more researchers. The topics include: - transition from combustion noise to thermoacoustic instability - development of an early-warning system by detecting the precursor of an instability - analytical flame models based on time-lags - Green's function approach for stability predictions from nonlinear flame models - intrinsic thermoacoustic modes - transport phenomena in swirl waves - model of the flame front as a moving discontinuity - development of efficient numerical codes for instability predictions - heat exchanger tubes inside a combustion chamber A substantial amount of valuable new insight was gained during this four-year project.